Small cationic boron and boron-nitrogen rings, synthesized from diboranes with charge-delocalizing guanidinate substituents - Vogler, Daniel; Horn, Julian; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2024)
We report the straightforward synthesis and characterization of small polycationic boron and boron-nitrogen rings, stabilized by charge-delocalizing guanidinate substituents. Reaction between a ditriflato-diborane with two electron-donating bridging bicyclic guanidinate substituents and the corresponding dihydrido-diborane leads to a dicationic B4 ring with a 4c,4e-bond in the planar rhomboid B4 skeleton. Reaction of the same ditriflato-diborane with the corresponding diazido-diborane gives a dicationic compound with a B4N2 core. On the basis of experimental data in combination with quantum-chemical calculations, pathways leading to these dicationic boron and boron-nitrogen rings are suggested, and further preliminary studies demonstrate the scope of this strategy for the synthesis of polycationic boron-nitrogen rings.
Gesehen am 15.01.2026